The First Experience of Creating Registers of Patients with Eye Diseases in Moscow Region - A. A. Ryabtseva; E. E. Grishina; O. M. Andruhina; A. A. Kovrizhkina; S. G. Sergushev; E. N. Homyakova; I. O. Alyabeva; K. B. Kunizheva (Oftalʹmologiâ, 2019)
This report is devoted to the problem of absence universal databases of patients with different chronic eye diseases and continuity of these patients between medical organizations. On the basis of MONIKI there has was held a prospective, observational cohort study of patients since 2016, with diagnoses: uveal melanoma — the first group of patients, degenerative States of the optic nerve and retina (multiple sclerosis, glaucoma) — the second group, — and vascular retinal diseases (venous occlusion, diabetic retinopathy) — the third group. There were 114 patients — in the first, 68 — in the second, 92 — in the third. There were developed statistically significant parameters of patients examination, adaptation of registers to application and increase of their efficiency continues to be corrected. All patients underwent standard ophthalmological examination, in addition-gonioscopy, ultrasound (ultrasound) in a and b-scan mode, including ultrasound biomicroscopy (UBM), optical coherence tomography (OCT), fluorescence angiography (FAG), computed tomography (CT) and/or magnetic resonance imaging (MRI) of the orbit. According to the indications, patients were examined by related specialists. For each patient group, prior results were obtained. They were late detection, untimely treatment and referral patients to other medical organizations, which proves the need to systematize patients with various pathologies and the subsequent continuity of medical organizations as for the timely detection of the disease, as for adequate and timely treatment not only at the local, but also at the regional or Federal levels. The integration of patients register with various ophthalmic diseases has a priority course in the development of healthcare in the Moscow region.